(untitled) (Journal of history, 2021)
The article discusses the beginning of the formation of regional relations between Kazakhstan and Central Asia in 1991-2011, interstate agreements, the definition of the border, the implementation of measures aimed at stabilizing the state of economic and social development of the states, as well as the issues of security of the countries, agreements on human rights, measures to regulate migration rules. The ancestors of the Kazakh diaspora who returned to Kazakhstan were forced to emigrate during the difficult times of the Soviet Union. Currently, their descendants immigrate to the Independent Re- public of Kazakhstan as to their historical homeland from different countries. It is studied that migration processes carried out on the basis of agreements between Kazakhstan and the states of Central Asia and compliance with UNO and international norms and requirements have acquired a regional and global character. In addition to the works of domestic and foreign authors, new documentary materials of the archive of the President of the Republic of Kazakhstan and the National Archive of the Republic of Kazakhstan were used to write this research article. As a result of the study, data on the location of the Kazakh diaspora arriving in the Republic of Ka- zakhstan in regional migration and their quantitative indicators from Kyrgyzstan, Turkey, Uzbekistan, Tajikistan, Iran and Afghanistan were given as well. Key words: Kazakhstan, Central Asia, Asian countries, Regional relations, Nations, Peoples, Ethnic groups, Diaspora, Migration, Repatriates.